2001
DOI: 10.1007/s101890170126
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation of poly(ethylenglycol)- b-poly(propylenglycol)-b-poly(ethylenglycol) copolymers above the glass transition temperature

Abstract: The complex dielectric permittivity has been measured for three poly(ethylenglycol)-bpoly(propylenglycol)-b-poly(ethylenglycol) copolymers with different content of poly(ethylenglycol) (15%, 33% and 80%), and increasing degree of crystallinity (0%, 10% and 20%, respectively). Only the noncrystalline sample shows the normal mode relaxation together with the segmental (α-relaxation) and the Johari-Goldstein (β-relaxation) modes. The crystalline samples show also polarization contributions due to the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…A second possibility for describing the E* results is to use an empirical function. This approach is frequently use in the analysis of the complex dielectric function 3* [11][12][13][14][15]. Taking into account that in DMTA experiments the mechanical strain and the stress play roles equivalent to those of the electrical displacement and of the electric field in the dielectric relaxation measurements, it can be concluded that the compliance D*Z1/ E* is the mechanical equivalent of 3* [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second possibility for describing the E* results is to use an empirical function. This approach is frequently use in the analysis of the complex dielectric function 3* [11][12][13][14][15]. Taking into account that in DMTA experiments the mechanical strain and the stress play roles equivalent to those of the electrical displacement and of the electric field in the dielectric relaxation measurements, it can be concluded that the compliance D*Z1/ E* is the mechanical equivalent of 3* [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of block copolymers, it has been found that the so-called normal mode of blocks such as poly(isoprene) or poly(propylene glycol) are different than in the corresponding homopolymers [10][11][12]. Also, the coexistence of an amorphous phase made of one of the comonomers, and a glassy or a crystalline phase formed by the other one may lead to the appearance of a rigid amorphous phase, with well differentiated dynamic properties [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Poly­( p -hydroxy­styrene) (PHOS) with narrow molecular weight distribution was utilized as the backbone polymer, and two different sequences of the monomer addition were conducted in order to achieve the two correspondingly inverse molecular architectures in regard to the side chains; i.e., either PPO or PEO was linked directly to the backbone. The morphology/structure, thermal properties, and the parameters that affect microphase separation in block copolymers based on poly­(propylene oxide) (PPO) and poly­(ethylene oxide) (PEO) have been studied extensively. Graft copolymers containing both PEO and PPO, however, have been reported scarcely regarding both their synthesis and physical properties. Inomata et al studied the morphology and packing manner of graft copolymers featuring rigid-rod-like poly­(γ-benzyl l -glutamate) (PBLG) main chains with grafted diblock copolymers of amorphous poly­(propylene glycol) (PPG) and crystalline poly­(ethylene glycol) (PEG) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the distribution of relaxation times is broader in copolymers than in homopolymers in the case of the normal mode. Moreno et al have studied PEO- b -PPO- b -PEO (PPO stands for poly(propylene oxide)) copolymers above T g , and both above and below the melting temperature of PEO, T m . They found that the distribution of relaxation times of the normal and the segmental relaxations depend on the PEO/PPO relative content.…”
Section: Introductionmentioning
confidence: 99%